2009
DOI: 10.2147/jaa.s4214
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of moderate to severe asthma: patient perspectives on combination inhaler therapy and implications for adherence

Abstract: Symptom control in patients with moderate to severe persistent asthma is essential to reduce the significant morbidity associated with the disease. Poor adherence to controller medications has been identified as a major contributing factor to the high level of uncontrolled asthma. This review examines patient perspectives on, and preferences for, controller medications (inhaled corticosteroid and long-acting β2-agonist combinations [ICS/LABA]), and how this may affect adherence to therapy. Fluticasone/salmeter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 56 publications
2
29
0
1
Order By: Relevance
“…In clinical practice, several factors can affect the ability of patients to achieve the clinical outcomes obtained in controlled conditions. The use of single-inhaler ICS/LABA combinations has been shown to increase patient adherence to treatment compared with the use of separate inhalers [3,4], which may help improve asthma outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical practice, several factors can affect the ability of patients to achieve the clinical outcomes obtained in controlled conditions. The use of single-inhaler ICS/LABA combinations has been shown to increase patient adherence to treatment compared with the use of separate inhalers [3,4], which may help improve asthma outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Fluticasone is a potent ICS [5] and formoterol is the fastest-acting inhaled LABA currently available for the treatment of asthma in a combination inhaler [6,7]. A rapid onset of action may be an important attribute of an ICS/LABA maintenance therapy for patients [4,8]; recent studies have suggested that therapies with a rapid onset of bronchodilation may encourage patient adherence to their treatment regimen [9,10]. Furthermore, fluticasone/formoterol has been shown in vitro to have a high fine particle fraction (FPF), to exhibit negligible flow-rate dependency [11], and has also demonstrated a slow, warm and prolonged aerosol plume [ [12]; unpublished data] factors which may correlate with corresponding high levels of lung deposition in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the use of single-inhaler ICS/LABA combinations has been shown to increase patients' treatment adherence compared with separate inhalers [Murphy and Bender, 2009], which may improve outcomes.…”
mentioning
confidence: 99%
“…Achieving asthma control is also hindered by perceptual barriers, contributing to reduced patient adherence to treatment regimens [8,9]. Studies have suggested that therapies with a rapid onset of bronchodilation may encourage adherence and, thus, improve real-world asthma outcomes [10,11].…”
mentioning
confidence: 99%